2002
DOI: 10.1021/es020697j
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Phosphate Amendments on Lead Biogeochemistry at a Contaminated Site

Abstract: Soil amendments can be used to cost-effectively reduce the bioavailability and mobility of toxic metals in contaminated soils. In this study a field demonstration was conducted at a Pb-contaminated site to evaluate the effectiveness of P-induced Pb immobilization. Phosphate was applied at a 4.0 molar ratio of P to Pb with three treatments: T1, 100% of P from H3PO4; T2, 50% P from H3PO4 + 50% P from Ca(H2PO4)2; and T3, 50% P from H3PO4 + 5% phosphate rock. Phosphate amendments effectively transformed soil Pb fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
132
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(151 citation statements)
references
References 33 publications
14
132
2
3
Order By: Relevance
“…For example, upon phosphate treatment from 5% to 10%, cerussite was reduced from 1.7% to 0.1%, whereas PbHPO 4 was increased from 0.2% to 3.4% (see Table 2). Note, many of previous studies have shown in situ or ex situ formation of most stable pyromorphite-like minerals (Pb 5 (PO 4 ) 3 X, X=Cl, OH, F) in the contaminated soils upon phosphate addition (Laperche et al 1997, Zhang & Ryan 1999, Cao et al 2002, Scheckel & Ryan 2004. However, pyromorphite-like minerals were not identified in the present study.…”
Section: Phosphate Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, upon phosphate treatment from 5% to 10%, cerussite was reduced from 1.7% to 0.1%, whereas PbHPO 4 was increased from 0.2% to 3.4% (see Table 2). Note, many of previous studies have shown in situ or ex situ formation of most stable pyromorphite-like minerals (Pb 5 (PO 4 ) 3 X, X=Cl, OH, F) in the contaminated soils upon phosphate addition (Laperche et al 1997, Zhang & Ryan 1999, Cao et al 2002, Scheckel & Ryan 2004. However, pyromorphite-like minerals were not identified in the present study.…”
Section: Phosphate Treatmentmentioning
confidence: 98%
“…Chemical-based S/S approach is based on the formation of thermodynamically stable and insoluble precipitate end-products with the contaminants. More effective chemical additives include phosphates and Fe-Mn oxides (Ma et al 1995, Hettiarachchi et al 2000, Basta et al 2001, Seaman et al 2001, Cao et al 2002. Phosphate has been proven to be effective in immobilizing Pb from labile soil Pb forms via formation of lead phosphate compounds such as pyromorphite-like minerals (Pb 5 (PO 4 ) 3 X, X=F, Cl, OH) by scavenging Pb from soluble Pb compounds such as cerussite (PbCO 3 ) and litharge (PbO) (Zhang & Ryan 1999, Cao et al 2002, Scheckel & Ryan 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate in soil may affect the chemical reactions of metals on mineral surfaces. Recent studies (Traina and Laperche, 1999;Cao et al, 2002) indicated that phosphate minerals, such as apatite, could sequester heavy metals, metalloids and radionuclide through adsorption and/or the formation of secondary PO 3À 4 precipitates, which remained stable under a wide range of geochemical conditions. Therefore, it is necessary to examine the influence of phosphate on the reactions of heavy metals on the surface of soil minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate minerals, i.e. phosphate rock (PR) and hydroxyapatite, have been shown to effectively immobilize Pb from various contam inated waters and soils (Cao et al, 2002;Ma et al, 1995;Ryan et al, 2001). Takeuchi and Arai (1990) suggested that Pb immobilization resulted from the formation of a more stable lead phosphate, such as Ca (10-x) Pb x (PO 4 ) 6 (OH) 2 via an ion exchange mechanism where aqueous Pb replaces Ca on the hydroxyapatite lattice.…”
Section: Introductionmentioning
confidence: 99%